Comparative evaluation of the remaining dentin volume following instrumentation with rotary, reciprocating, and hand files during root canal treatment in primary molars: An ex vivo study - İrem Eren; Berkant Sezer (Elsevier, 2024)
Background/purpose: The effectiveness of root canal treatments with different file systems in primary teeth is important in terms of clinical practice and the use of file systems that work with different principles in primary tooth pulpectomy is becoming widespread. The amount of remaining dentin in the coronal region of the root is important in terms of the prognosis of the tooth and the long-term success of the treatment in teeth that have undergone root canal treatment. The aim of this study was to evaluate the remaining dentin volume in the coronal part of the root after the use of rotary, reciprocating, and conventional hand files in primary tooth pulpectomy. Materials and methods: A total of 30 primary molars were divided into three groups. In each group, the preparations were made with three different file types: WaveOne Gold, which works with reciprocating motion; TruNatomy, which works with rotational motion; and conventional hand files. The three-dimensional images were evaluated for remaining dentin volume in the 2-mm coronal part of the root. Group means were compared using one-way analysis of variance, and post hoc analyses were performed with the Tukey test. Results: There was no statistically significant difference between the groups in terms of preoperative and postoperative dentin volume (P > 0.05). The mean difference after preparation was observed the most in the WaveOne Gold group and the least in the TruNatomy group. When the mean percentage differences were evaluated, it was observed that statistically significantly more dentin volume was preserved after the preparation with TruNatomy than with WaveOne Gold (P = 0.021). Conclusion: In primary tooth pulpectomy, file systems working with rotational motion can be preferred over file systems working with reciprocating motion in preserving the amount of dentin in the 2-mm coronal part of the root.